Photocatalytic activity of zinc oxide nanoparticles prepared by laser ablation in a decomposition reaction of rhodamine B - Gavrilenko, Ekaterina A.; Goncharova, Darya A.; Lapin, Ivan N.; Gerasimova, Marina A.; Svetlichnyi, Valerii A. (Russian physics journal)
The development of the routes for synthesizing photocatalysts and the methods for investigating their properties is very appealing for applications in ecology and renewable energy production. Zinc oxide is one of the promising photocatalytic materials. In this study, ZnO nanopowders are produced by pulsed laser ablation (Nd:YAG laser, 1064 nm, 7 ns) in water and air, followed by their heat treatment. The structure and composition of the resulting powders are examined using transmission electron microscopy, X-ray diffraction, and differential scanning calorimetry. The nature of the defect states of nanoparticles is investigated using fluorescence spectroscopy. Their photocatalytic activity is tested during photodegradation of Rhodamine B under excitation by the broadband visible and UV-visible light. The influence of the composition and morphology of zinc oxide and the nature of defect states on its photocatalytic activity is discussed.